EFFECT OF PRETREATMENTS ON SESAME CAKE PROTEIN HYDROLYSIS BY ALCALASE - Demirhan, E.; Apar, D. Kilic; Ozbek, B. (PLAPIQUI(UNS-CONICET), 2015)
In the present work, the effects of pretreatments on hydrolysis of sesame cake protein and enzyme stability were investigated. Heat, microwave and sonic pretreatments were applied to sesame cake protein as pretreatments before the enzymatic hydrolysis reaction. The sesame cake protein was hydrolyzed by Alcalase enzyme.
Keywords: sesame cake protein; Alcalase; heat pretreatment; microwave pretreatment; sonic pretreatment; ENZYMATIC-HYDROLYSIS; SOLUBILIZATION; GLUTEN; Engineering